부호 기반 양자 내성 암호의 이진 필드 상에서 곱셈 연산 양자 게이트 구현 - 최승주(Seung-Joo Choi); 장경배(Kyong-Bae Jang); 권혁동(Hyuk-Dong Kwon); 서화정(Hwa-Jeong Seo) (한국정보통신학회논문지, 2020)
The age of quantum computers is coming soon. In order to prepare for the upcoming future, the National Institute of Standards and Technology has recruited candidates to set standards for post quantum cryptography to establish a future cryptography standard. The submitted ciphers are expected to be safe from quantum algorithm attacks, but it is necessary to verify that the submitted algorithm is safe from quantum attacks using quantum algorithm even when it is actually operated on a quantum computer. Therefore, in this paper, we investigate an efficient quantum gate implementation for binary field multiplication of code based post quantum cryptography to work on quantum computers. We implemented the binary field multiplication for two field polynomials presented by Classic McEliece and three field polynomials presented by ROLLO in generic algorithm and Karatsuba algorithm. 양자 컴퓨터의 시대가 점점 현실로 다가오고 있다. 이에 대비해 미국 국립 표준 기술 연구소에서는 양자 알고리즘으로부터 내성이 있는 양자 내성 암호의 표준을 정하기 위해 후보군을 모집했다. 제출된 암호들은 양자 알고리즘으로부터 안전할 것으로 예상이 되지만 알고리즘이 실제 양자 컴퓨터상에서 작동이 되었을 때에도 양자 알고리즘의 공격으로부터 안전한지 검증을 할 필요가 있다. 이에 본 논문에서는 부호 기반 양자 내성 암호의 이진 필드 상에서의 곱셈 연산을 양자 컴퓨터에서 작동될 수 있게 양자 회로로 구현하였고 해당 회로를 최적화 하는 방안에 대하여 설명한다. 구현은 대표적인 부호 기반 암호인 Classic McEliece에서 제시하는 2개의 필드 다항식과 ROLLO에서 제시하는 3개의 필드 다항식에 대하여 일반 곱셈 알고리즘과 카라추바 곱셈 알고리즘으로 구현하였다.